Blucher Design Proceedings 2018
DOI: 10.5151/sigradi2018-1642
|View full text |Cite
|
Sign up to set email alerts
|

Aplicability of 2D and 3D isovists and visibility graph analysis for evaluating urban vulnerability to crime: the case of Boa Viagem, in Recife

Abstract: xxii congresso da sociedade iberoamericana de gráfica digital 22th conference of the iberoamerican society of digital graphics 07|08|09|novembro|2018 iau usp | são carlos | sp br

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Pereira Bezerra de Melo Junior and Canuto da Silva [51] used a similar approach to examine the isovist properties of locations that experienced thefts and robberies in a neighborhood in Recife, Brasil. Results of the correlational analysis showed that crimes occurred in areas with low occlusivity values, lower isovist area, lower isovist perimeter, and low visual integration.…”
Section: Visibility and Crimementioning
confidence: 99%
“…Pereira Bezerra de Melo Junior and Canuto da Silva [51] used a similar approach to examine the isovist properties of locations that experienced thefts and robberies in a neighborhood in Recife, Brasil. Results of the correlational analysis showed that crimes occurred in areas with low occlusivity values, lower isovist area, lower isovist perimeter, and low visual integration.…”
Section: Visibility and Crimementioning
confidence: 99%